Assessing the adoption and application of the Namibian biosafety labelling regulations and determining their impact on Namibian food and feed importers - Mungeyi, Paulus; Chimwamurombe, Percy Maruwa; Kangueehi, Grace Nandesora (Frontiers in Bioengineering and Biotechnology, 2023)
The study was carried out to investigate the implications of the Namibian biosafety regulations on Namibian food and feed importers. After the Biosafety Act, 2006 (Act No. 7 of 2006), the biosafety regulation was gazetted in 2016, which saw the implementation of the national framework, the impact of food and feed importers was not known. The objective of the study was to assess the adoption and application of the national biosafety labelling regulations by food and feed importers. In addition, the impacts of these regulations on Namibian food and feed importers were assessed. The study used a structured online and hard copy survey questionnaire based on responses from 340 Namibian importers of food and feed products from eight identified Namibian regions: Khomas,